1990
DOI: 10.1111/j.1365-2958.1990.tb00719.x
|View full text |Cite
|
Sign up to set email alerts
|

Pyoverdin‐facilitated iron uptake in Pseudomonas aeruginosa: immunological characterization of the ferripyoverdin receptor

Abstract: A purified polyclonal antiserum directed against the isolated main 80 kD IROMP (iron-regulated outer-membrane protein) from Pseudomonas aeruginosa PAO1 detected only the 80 kD polypeptide of outer-membrane proteins from PAO1 cells grown in iron deficiency in Western blots. It was also shown to inhibit the uptake of 59Fe pyoverdin by PAO1 cells as well as its binding to purified outer membranes. Immunofluorescence experiments with intact PAO1 cells confirmed that the receptor is present only at the surface of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…As previously shown for P. aeruginosa ATCC 15692 and ATCC 27853, this procedure allows recognition of strains having a PVD-mediated iron uptake system identical to the ones of the two typestrains (Cornelis et al, 1989a) by specifically revealing the ferripyoverdine outer-membrane receptor as demonstrated for P. aeruginosa ATCC 15692 (Meyer et al, 1990). The anti-P. aeruginosa Pa6-IROMP antiserum behaved the same, reacting strongly with the 80 kDa IROMP of strain Pa6, while it cross-reacted only slightly with one or two outer-membrane- shown in Table 3.…”
Section: Siderotyping By Ferripyoverdine Outer-membrane Receptor Immumentioning
confidence: 80%
See 1 more Smart Citation
“…As previously shown for P. aeruginosa ATCC 15692 and ATCC 27853, this procedure allows recognition of strains having a PVD-mediated iron uptake system identical to the ones of the two typestrains (Cornelis et al, 1989a) by specifically revealing the ferripyoverdine outer-membrane receptor as demonstrated for P. aeruginosa ATCC 15692 (Meyer et al, 1990). The anti-P. aeruginosa Pa6-IROMP antiserum behaved the same, reacting strongly with the 80 kDa IROMP of strain Pa6, while it cross-reacted only slightly with one or two outer-membrane- shown in Table 3.…”
Section: Siderotyping By Ferripyoverdine Outer-membrane Receptor Immumentioning
confidence: 80%
“…The purification of bacterial outer membranes and visualization of the iron-regulated outermembrane proteins (IROMPs) be denaturating PAGE, the preparation of crude and partially purified rabbit polyclonal antisera raised against the main IROMP of P. aeruginosa strains and the immunodetection of the IROMPs by Western blotting have been described previously (Cornelis et al, 1989a ;Meyer et al, 1990). The large number of strains investigated in the present study required a rapid and easy method of outer 1983CIP 1994CIP 1983CIP 1983CIP 1983CIP 1983CIP 1994(ATCC 23268) CIP 1994(ATCC 23267) CIP 1983CIP 1983CIP 1994CIP 1994CIP 1994CIP 1983CIP 1983CIP 1983CIP 1983CIP 1983CIP 1983CIP 1983CIP 1994CIP 1983CIP 1983CIP 1983CIP 1983CIP 1983CIP 1983CIP 1983CIP 1983 t As indicated in the catalogues or in the literature; -, no information available.…”
Section: Methodsmentioning
confidence: 99%
“…aeruginosa strains, Cornelis et al (1989) noted three pyoverdin uptake groups and polyclonal antisera raised against an 80 kDa IROMP reacted only against strains producing the same siderophore. This antiserum was subsequently shown to inhibit ferri-pyoverdin transport in this strain, confirming that the 80 kDa IROMP was a transporter (Meyer et al, 1990). Poole et al (1991) have identified a 90 kDa IROMP ferri-pyoverdin transporter in the pyoverdin-deficient strain 6609.…”
Section: Introductionmentioning
confidence: 78%
“…The purification procedure for pyoverdines and electrophoretic analysis were as described previously (Meyer & Abdallah, 1978). The protocol used for iron uptake experiments has been described elsewhere (Meyer et a/., 1990). UV-visible spectra were obtained from a Uvikon 930 (Kontron) spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%